Can the velocity profile in the bench press and the bench pull sufficiently estimate the one repetition maximum in youth elite cross-country ski and biathlon athletes? - Wagner, C.-M.; Keiner, M., Puschkasch-Möck, S.; Wirth, K.; Schiemann, S.; Warneke, K. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Introduction In recent years, load-velocity profiles (LVP) have been frequently proposed as a highly reliable and valid alternative to the one-repetition maximum (1RM) for estimating maximal strength and prescribing training loads. However, previous authors commonly report intraclass correlation coefficients (ICC) while neglecting to calculate the measurement error associated with these values. This is important for practitioners, especially in an elite sports setting, to be able to differentiate between small but significant changes in performance and the error rate.